Performance Analysis of WADGPS System for Improving Positioning Accuracy - So, Hyoungmin; Jang, Jaegyu; Lee, Kihoon; Park, unpyo; Song, Kiwon (Journal of Positioning, Navigation, and Timing, 2016)
The Wide Area Differential Global Positioning System (WADGPS) that uses a number of Global Navigation Satellite System (GNSS) reference stations are implemented with various types and provide services as it can service a wide range of areas relatively. This paper discusses a constellation design of reference stations and performance analysis of the WADGPS. It presented performance results of static and dynamic users when wide area correction algorithm was applied using eight reference stations. KCI Citation Count: 2